Unraveling the immune mechanisms and therapeutic targets in lung adenosquamous transformation - Xu, Haiyan; Yang, Ying; Wang, PingLi; Lin, Shengnan; Zhang, Xiaochun; Ni, Huiwen; Xu, Zhiyong (Frontiers in Immunology, 2025)
Adenocarcinoma-to-squamous cell carcinoma transformation (AST) induces drug resistance in patients with lung adenocarcinoma (LUAD), often resulting in unfavorable clinical outcomes. In recent years, it has been found that alterations in the tumor immune microenvironment (TIME) during adenosquamous carcinoma trans-differentiation also influence the efficacy of immunotherapy. Moreover, the aberrant expression and activation of several driver genes for AST lead to abnormal infiltration and function of immune cell by remodeling the cellular inflammatory phenotype. In this review, we will systematically present the changes in the TIME and molecular regulatory mechanisms during adenosquamous carcinoma differentiation, aiming to gain a better understand of the function of immune cells during this process and the potential value of combining immunotherapy to enhance the treatment of non-small cell lung cancer (NSCLC).